Beneath the burning issue of Beadica: public policy and context astride the corporate veil - van Wijk, Andrew Murray (Department of Commercial Law, 2022)
The metaphors used when speaking of equity are rather colourful. One reads, amused, of the ‘burning issue', the ‘shibboleth' and the ‘sacred cow'. But these metaphors, used as they are in a discipline which tends away from the dramatic in its everyday formulations, only lend more emphasis to the gravity of the quandary. A widening gap between views on the proper method for the judicial control of contract, be it a balanced public policy or unfettered equity, caused true discordance between the Supreme Court of Appeal and the Constitutional Court, our two highest courts. In Beadica 231 CC and Others v Trustees, Oregon Trust and Others 2020 (5) SA 247 (CC) the Constitutional Court largely settled matters when it came down on the side of public policy. This no doubt caused surprise in some quarters, given its dicta in earlier cases. Nevertheless it settled the question of which legal device was to be used. Public policy is to have sole mandate and the ‘burning issue' was, apparently, doused. As to the nature of this legal device, it is a truism that the content of public policy changes with the times, but in the constitutional republic that South Africa is today the Constitution is an unassailable source of its content and values. This makes our interpretation of what it demands in the contractual context of huge import. The tension meant that instead of the cut and thrust of hard precedent, cases were largely evaluated for their tendency to reflect the increasing public facet to this most cloistered sanctum of private law. Brought back to the challenge in Beadica, this study traces in Chapters II and II something that went largely unnoticed in the shadow of the contract tectonics then on the move: the historical antecedents and theoretical underpinnings of the public interest aspect of public policy had culminated in a tension with separate legal personality. In Beadica the parties were juristic persons yet claimed the benefit of historical, substantive equality in their contractual affairs. This claim was weighed but found wanting in the Constitutional Court - but it is this ember, the implications of the corporate veil being lifted in the evaluation of equality, that represents, if not something new, then the confirmation of what some have long argued for - or suspected. Chapter IV accordingly argues that Beadica is a confirmation of the imperative of substantive equality in the contractual context, albeit that the bar has been set very high in light of the dangers. Chapter V briefly explores the adjacent legal routes by which similar outcomes could be reached before reflecting on the general historical treatment that is the bedrock of this piece.